2013
DOI: 10.1103/physrevb.87.115137
|View full text |Cite
|
Sign up to set email alerts
|

Zero-bias anomaly in a two-dimensional granular insulator

Abstract: We compare tunneling density of states (TDOS) into two ultrathin Ag films, one uniform and one granular, for different degrees of disorder. The uniform film shows a crossover from Altshuler-Aronov (AA) zero bias anomaly to Efros Shklovskii (ES) like Coulomb gap as the disorder is increased. The granular film, on the other hand, exhibits AA behavior even deeply in the insulating regime. We analyze the data and find that granularity introduces a new regime for the TDOS. While the conductivity is dominated by hop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The zero bias anomaly in tunneling spectra may stem from various reasons, such as electron-electron interactions [18], Coulomb blockade [19], hopping dominated conductance between the clusters of disordered metal grains [20], Kondo scattering from magnetic moments, Giaever-Zeller two-step tunneling process, etc. In electron-doped cuprates, Alff et al studied the tunneling spectra of Pr 2−x Ce x CuO 4 and La 2−x Ce x CuO 4 , and reported a T * that is smaller than T c , pointing to a competing order below the superconducting dome [15].…”
mentioning
confidence: 99%
“…The zero bias anomaly in tunneling spectra may stem from various reasons, such as electron-electron interactions [18], Coulomb blockade [19], hopping dominated conductance between the clusters of disordered metal grains [20], Kondo scattering from magnetic moments, Giaever-Zeller two-step tunneling process, etc. In electron-doped cuprates, Alff et al studied the tunneling spectra of Pr 2−x Ce x CuO 4 and La 2−x Ce x CuO 4 , and reported a T * that is smaller than T c , pointing to a competing order below the superconducting dome [15].…”
mentioning
confidence: 99%